2012
DOI: 10.1002/hed.23157
|View full text |Cite
|
Sign up to set email alerts
|

Readability assessment of online thyroid surgery patient education materials

Abstract: Readability scores for online thyroid surgery materials are higher (i.e., more difficult) than the recommended levels. However, readability is only one aspect of comprehension. Written information should be designed with that fact in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 21 publications
(74 reference statements)
5
82
1
1
Order By: Relevance
“…It is estimated that 34% of adults in the United States have only basic or below basic reading literacy (10) with an inverse relationship between age and reading skill level, even when adjusted for cognitive impairment or years of schooling (11). Furthermore, it has been determined that the average reading age in the United States is between a seventh-and eighth-grade level (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 34% of adults in the United States have only basic or below basic reading literacy (10) with an inverse relationship between age and reading skill level, even when adjusted for cognitive impairment or years of schooling (11). Furthermore, it has been determined that the average reading age in the United States is between a seventh-and eighth-grade level (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Information is categorized as being of ''easy'' readability if written at this level, ''average'' if assessed between seventhand ninth-grade readability, and ''difficult'' if above this (Table 1) (2). Previous studies have evaluated the readability of online patient information for a variety of medical conditions, including heart disease, cancer, stroke, chronic obstructive pulmonary disease, diabetes mellitus, thyroid surgery, craniofacial conditions, age-related macular degeneration, orthopedic conditions, dermatological problems, abdominal aortic aneurysm, epilepsy, and Parkinson's disease (Table 2) (2,4,8,9,(12)(13)(14)(15)(16)(17)(18)(19)(20). Each of these studies determined that the readability of most online patient education materials, using a variety of readability scores, is less than that recommended by USDHHS.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng and Yu have reported on the readability of electronic health records compared to Wikipedia pages related to diabetes and found that readability measures often do not align with user ratings of readability [22]. A common finding of these studies is that, in general, health content available on Web pages is often hard to understand by the general public; this includes content that is retrieved in topranked positions by current commercial search engines [4,5,6,7,8,9].…”
Section: Related Workmentioning
confidence: 99%
“…These measures generally rely on surface-level characteristics of text, such as characters, syllables and word counts (missing citation). While these measures have been widely used in studies investigating the understandability of health content retrieved by search engines (e.g., [4,5,6,7,8,9,18,21]), our preliminary work found that these measures are heavily affected by the methods used to extract text from the HTML source [13]. We were able to identify specific settings of an HTML preprocessing pipeline that provided consistent estimates, but due to the lack of human assessments, we were not able to investigate how well each HTML preprocessing pipeline correlated with human assessments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation